THE EFFECTIVENESS OF PROBLEM BASED LEARNING MODEL IN SCIENCE LEARNING ON CRITICAL THINKING SKILLS OF FIFTH GRADE STUDENTS - Diah Anjani Putri; Zulfadewina (Universitas Majalengka, 2023)
The development of the times requires students to master 4 skills, one of the skills that must be mastered is Critical Thinking. The reality that occurs at SDN Dukuh 01 is that the critical thinking skills of grade V students are low. This research is to determine the effectiveness of Problem-Based Learning model in Science Learning on Critical Thinking Skills of 5th Grade Students at SDN Dukuh 01 in the even semester of the 2022/2023 school year. The research method used is quantitative with a research design of Non-equivalent Control Group Design. The total population in this study was 130 students, with a total sample of 52 students. The data collection technique in this study was to use a test instrument with 10 essay questions. Data analysis techniques using the normality test, homogeneity test, and t test. The Validity testing used the Pearson Colleration formula with eight valid and two invalid questions. The calculation of critical thinking skills data according to the indicators obtained the following average results: the experimental class of 83.25 and the control class of 64.74. It can be seen that the percentage results in the experimental class are higher than in the control class. Testing the analysis requirements, namely the normality and homogeneity tests using the SPSS 22.0 program obtained a value (sig.) > 0.05, which means that the data is normally distributed and homogeneous. The hypothesis testing used the independent sample t-test on SPSS 22.0, obtaining a value (sig.) 0.000; thus, Ha is accepted, and H0 is not accepted. It can be concluded that the use of the Problem-Based Learning model in science learning is effective on the critical thinking skills of five grader students at SDN Dukuh 01. Perkembangan zaman menuntut siswa untuk menguasai 4 keterampilan, salah satu keterampilan yang harus dikuasai adalah Berpikir Kritis. Realita yang terjadi di SDN Dukuh 01 keterampilan berpikir kritis siswa kelas V rendah. Studi ini bermaksud guna mengetahui efektivitas model problem based learning pada pembelajaran IPA akan keterampilan berpikir kritis siswa kelas V SDN Dukuh 01 pada semester genap tahun ajaran 2022/2023. Sistem penelitian yang dipergunakan ialah sistem kuantitatif menggunakan desain penelitian dan berbentuk nonequivalent control group design. Jumlah populasi pada penelitian ini sebanyak 130 peserta didik, dengan jumlah sampel sebanyak 52 peserta didik. Teknik pengumpulan data dalam penelitian ini adalah menggunakan instrument tes dengan 10 butir soal essay. Teknik analisis data menggunakan uji normalitas, uji homogenitas, dan uji t. Pengujian validitas mempergunakan rumus Korelasi pearson sebanyak sepuluh butir soal esai dengan delapan soal valid dan dua soal tidak valid. Perhitungan data keterampilan berpikir kritis sesuai indikator diperoleh rerata hasil kelas eksperimen sejumlah 83,25 dan kelas kontrol berjumlah 64,74, maka tampak bila persentase kelas eksperimen di atas kelas kontrol. Pengujian persyaratan analisis, yaitu uji normalitas dan homogenitas mempergunakan program SPSS 22.0 didapat nilai (sig.) > 0,05 yang berarti data berdistibusi normal dan homogen. Pengujian hipotesis mempergunakan uji independent sample t-test pada SPSS 22.0 memperoleh nilai (sig.) 0,000, maka Ha diterima dan H0 tidak diterima. Hasil itu memberi simpulan bila pemakaian model problem based learning efektif terhadap keterampilan berpikir kritis peserta didik pada pembelajaran IPA siswa kelas V SDNegeri Dukuh 01.